Exploring the cortical habituation in migraine patients based on contingent negative variation - Ning, Jinru; Zhang, Yongxiang; Wang, Yan; Liu, Chang; Cheng, Yingying; Zhu, Mingqin; Dong, Ming; Yang, Xin; Lv, Yudan (Frontiers in Neurology, 2023)
Objective: Cognitive dysfunction has frequently been found in patients with migraine. And the so-called contingent negative variation (CNV) and EEG power spectral densisity may be the best choice to explore the underlining pathophysiology, such as cortical inhibition and habituation. Methods: Thirty migraine patients without aura and healthy controls matched for sex, age, and education were recruited separately for CNV recording. The amplitudes, latencies, squares of different CNV components such as oCNV, iCNV and tCNV, PINV have been selected and analyzed. Behavioral data such as manual reaction time (RT) has been analyzed. We used the Person correlation coefficient R to analyse the different ERP components in relation to clinical characteristics. Multiple regression analysis was performed for the migraine group. Spectral analysis of EEG data from all channels using fast Fourier transform (FFT). Results: The migraine group had longer A-latency, C-latency, iCNV-latency than control group. The migraine group had higher iCNV-amplitude, oCNV-amplitude and tCNV-amplitude than control group, especially located in occipital area. The iCNV-square, oCNV-square, tCNV-square or PINV-square in migraine group was significant larger than control group. Different correlations have been found between clinical characteristics and ERP components. The delta or theta activity in migraine group was statistically decreased than control group. Discussion: Our study has revealed that migraine attacks may influence the responsivity, pre-activation, habituation and cortical inhibition, not only on behavior level, but also on the electrophysiological level. Abnormal changes in cortical habituation and inhibition can be interpreted as CNV components. Additionally, correlation analysis has been found between age, clinical course, frequency, pain intensity, duration and CNV components. Thus, repetitive migraine attacks attenuate cortical inhibition and impairs executive function.